PELAKSANAAN AKUNTANSI PERTANGGUNG JAWABAN SEBAGAI ALAT PENGENDALIAN BIAYA PADA PERUM PEGADAIAN CABANG SELAYAR - Erwin Horas (AkMen JURNAL ILMIAH, 2011)
This study aims to find out the implementation of the budget in the accounting system on a screen and Perum pegadain branch To find out the cause of the difference between the budgeted cost, with the realization of cost and its relationship with the person responsible for occurrence of such costs. The analytical method used is the comparative method is to Classify types of costs and explain the causes of variances between the budget to realization. The results showed the budget office occurred variance Pawnshop profit (the cost of stationery, office supplies, etc.) on some object cost and loss variance (the cost of promotion, advertising, etc.) to another object that this is caused by circumstances particular. The analysis showed the hypothesis was not proven that the Pawnshop Selayar not use the budget as a tool to control costs, because the Pawnshop to cost efficiency in carrying out their business activities. Controllable and uncontrollable costs are not separated in the company. This is because the company has not merelisasikan accountability report for each cost center accountability.